2017
DOI: 10.1002/cpp.2100
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and dissociation as mediators of the link between childhood trauma and psychotic experiences

Abstract: Exposure to childhood trauma has been implicated in the development of paranoia and hearing voices, but the mechanisms responsible for these associations remain unclear. Understanding these mechanisms is essential for ensuring that targeted interventions can be developed to better support people experiencing distress associated with paranoia and voices. Recent models have proposed that dissociation may be a mechanism specifically involved in the development of voices and insecure attachment in the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 54 publications
3
73
0
3
Order By: Relevance
“…Five different measures of attachment were used across the 12 studies. Six studies (Korver‐Nieberg et al ., ; Pearce et al ., ; Ponizovsky et al ., ; Sitko, Varese, Sellwood, Hammond, & Bentall, ; Strand, Goulding, & Tidefors, ; Wickham et al ., ) used The Relationship Questionnaire (RQ: Bartholomew & Horowitz, ) to measure attachment subtypes (secure, dismissing, pre‐occupied, fearful). Two studies (Korver‐Nieberg et al ., ; Wickham et al ., ) created superordinate attachment anxiety and avoidance dimensions by yielding scores from the four RQ subtypes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five different measures of attachment were used across the 12 studies. Six studies (Korver‐Nieberg et al ., ; Pearce et al ., ; Ponizovsky et al ., ; Sitko, Varese, Sellwood, Hammond, & Bentall, ; Strand, Goulding, & Tidefors, ; Wickham et al ., ) used The Relationship Questionnaire (RQ: Bartholomew & Horowitz, ) to measure attachment subtypes (secure, dismissing, pre‐occupied, fearful). Two studies (Korver‐Nieberg et al ., ; Wickham et al ., ) created superordinate attachment anxiety and avoidance dimensions by yielding scores from the four RQ subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were rated as strong (Sitko et al ., ; Wickham et al ., ) as these controlled for several relevant confounders. Three studies received a moderate rating (Berry et al ., ; Pearce et al ., ; Ponizovsky et al ., ) as confounders had been controlled for in one or two relevant analyses, but not all. Notably, only two studies used additional clinician measures to corroborate self‐report attachment (Berry et al ., ) and self‐report paranoia (Dozier & Lee, ), enabling some assessment of social desirability bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we also found full mediation of general dissociation, and specifically, of absorption and depersonalization, between the memories of these threatening and submissiveness experiences and hallucination proneness. Previous studies have also found that dissociation generally mediates between traumatic interpersonal experiences, more specifically, sexual abuse, and hallucinations in subjects with psychiatric pathology (Pearce, Simpson, Berry, Bucci, Moskowitz & Varese, ; Varese, Barkus & Bentall, ) and in subjects with no psychiatric pathology (GĂłmez & Freyd, ). Our results are coherent with those found by Perona‐GarcelĂĄn et al .…”
Section: Discussionmentioning
confidence: 99%
“…The latter finding stands in contrast to the well‐established relationship between childhood adversity and the severity of hallucinations in people with psychotic disorders (Bailey et al, ). Similarly, dissociative experiences have been strongly related to voice hearing in psychotic disorders, and might be a mediating factor in the relationship between trauma and hallucinations in this group (Pearce et al, ; Pilton, Varese, Berry, & Bucci, ). However, in a study of 23 adults with BPD, no association was reported between dissociation and psychotic symptoms in general, or between dissociation and hallucinations (Tschoeke et al, ).…”
Section: Introductionmentioning
confidence: 98%